Dying to be me [compact disc, unabridged] : my journey from cancer, to near death, to true healing - Moorjani, Anita, 1959- (Hay House Audio, 2012)
"In this truly inspirational audio book, Anita Moorjani relates how, after fighting cancer for almost four years, her body began shutting down--overwhelmed by the malignant cells spreading throughout her system. As her organs failed, she entered into an extraordinary near-death experience where she realized her inherent worth--and the actual cause of her disease. . . . After years of struggling to forge her own path while trying to meet everyone else's expectations, she had the realization, as a result of her epiphany on the other side, that she had the power to heal herself--and that there are miracles in the Universe that she had never even imagined"--Container.